Tactics or strategies? Exploring everyday conditions to facilitate implementation of an Indigenous graduate attributes project. Issue 4 (4th July 2019) - Page, Susan; Trudgett, Michelle; Bodkin-Andrews, Gawaian
ABSTRACT: In 2017 Universities Australia (UA), the peak body representing Australian universities released its Indigenous Strategy 2017–2020 . The document unites universities together in common goals for Indigenous achievement, filling a notable gap in the Australian higher education landscape. The Strategy outlines a comprehensive plan for enhanced Indigenous outcomes in critical areas of higher education including student access and success, graduate research, and community engagement. This paper focuses on the implementation of Indigenous curriculum for all Australian university graduates which is a key aspect of the Strategy . The changing Indigenous higher education landscape invites the nuanced analysis that critical examination of universities, as organisations, might elicit. Drawing on de Certeau's notion of tactics and strategies, the paper examines the policy and cultural climate of an Australian university which supports an Indigenous Graduate Attribute curriculum project.